The Effect Of Different Flexibility Studies On Performance Of Taekwondo - Duygu Sevinç Yılmaz (Selcuk University, 2021)
In order to be successful in Taekwondo, the athlete must have optimum flexibility in order to maintain his strength and speed, to attack and defend, to apply a combined technique, to minimize the injury rate and to recover quickly afterwards. Muscle groups that are not sufficiently flexible can affect performance negatively. Flexibility exercises have become indispensable for training programs not only for athletes in taekwondo, but also for athletes of all levels and branches. The athlete must have a comprehensive ROM to be able to perform taekwondo-specific techniques efficiently. In addition to benefiting athletic performance, flexibility also has general health-improving effects. According to the existing literature, in order for flexibility studies to be beneficial, the working method and performance status should be well determined. In parallel, we can say that adjusting the number of set-repeats, the auxiliary materials used, the variety of movements according to the characteristics of the sample group and the motoric feature that is desired to be developed can be beneficial for performance development.